Translation and validation of Malay version 5-items brief illness perception questionnaire, BIP-Q5 towards COVID-19 among Malaysian nurses - Pasi, Hafizah; Kamaruzaman, Nor Azam; Ahmad Basri, Nadzirah; A Manan, Nur Hakimah; Nasreen, Hashima E (Scientific Research Publishing (SCIRP), 2022)
Introduction: Currently, own individual perception is recognized as one of the important factors in the prevention of disease, including coronavirus disease, COVID-19. Given the massive impact of COVID-19 on all population’s life, including nurses as one of the main health services providers in the country, this study aims to translate and validate the Malay Version 5-Items Brief Illness Perception Questionnaire, BIP-Q5 towards COVID-19 among Malaysian nurses. Materials and Methods: Forward and backward translations and pretesting of the BIP-Q5 to Malay were conducted among nurses, subject matter experts, and language professionals. The validations process was elicited through an online cross-sectional study involving 56 nurses based on a ~10:1 subject-to-items ratio sample size estimations. Results: The principal component analysis (PCA) revealed one best component with eigenvalues more than one, confirming the questionnaire’s original version. There are five items within the single component, and all are with weightage of over 43%. The scree plot supported the findings, which showed that at least one factors are suitable to be retained. The overall Cronbach’s α coefficient was 0.7 and the intraclass correlation coefficient was 0.659. The Kaiser-Meyer-Olkin was 0.655, and Bartlett’s test of sphericity p-value was <0.001. Conclusion: This study showed that the translated Malay Version 5-Items Brief Illness Perception Questionnaire, BIP-Q5 has a good psychometric property, and is a valid and reliable tool to be used to measure illness perceptions towards COVID-19 among Malaysian nurses.